Thermodynamic parameter analysis of water vapor adsorption process of fly ash concrete material - Lianjuan Miao; Chenggong Lu; Chujie Jiao (Case Studies in Construction Materials, 2023)
Experimental research on water vapor adsorption performance of concrete with different class Ⅱ fly ash contents is carried out in this paper. Time-varying response curves of water vapor adsorption of fly ash concrete in five different humidity environments were obtained. According to the empirical formula of the thermodynamic parameters of water vapor adsorption of cement-based materials, the thermodynamic parameters of the water vapor adsorption process of fly ash concrete materials are calculated. The calculation method of the thermal kinetic parameters of water vapor adsorption for fly ash concrete materials is proposed; Influence of different fly ash contents with 10%, 20% and 30% mass percentage of cement and water-cement ratio on the water vapor adsorption characteristics of concrete materials is analyzed; The error between the second-layer adsorption energy and the condensation enthalpy of water vapor is calculated, and the rationality of the approximate calculation is analyzed. It is noted that (1) Water vapor adsorption characteristics of concrete materials are related to the water-cement ratio. With the water-cement ratio decreases, the adsorption capacity of concrete material increases. (2) Reasonable formula for calculating the number of saturated adsorption layers n of water vapor suitable for concrete materials is recommended. (3) Taking the condensation enthalpy of water vapor as the adsorption enthalpy of the second layer and subsequent layers reasonable to determine the dynamic parameters of the water vapor adsorption process of concrete.